The Struggles Against Discrimination Reflected In Till (2022) Movie - latifah, Nurul; Ramadhina, Retno; Mashuri, Mashuri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The writer chose this topic and Till movie as the main sources that are analyzed because the writer sees something important that can be learned from this movie. In this research, the writer analyzes the types of discrimination and the types of responses against discrimination that happens to Emmet Till that occurs in the Till movie. There are main characters who experience discrimination, namely Bo. The purpose of this research is to explain the types of discrimination experienced by black American boy and to find out how Emmet Till responded against the discrimination. The writer used a sociological approach and qualitative descriptive methods to carry out this research. The data in this research comes from speech and actions in movies related to discrimination issues. Based on the result of the analysis, the writer found that there was only black discrimination that occurred in the movie. Discrimination in the movie is carried out by white people against black Americans.